2021
DOI: 10.3390/land10101104
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Carbon Credits to Finance Wildfire Risk Reduction Forest Management in Mediterranean Landscapes

Abstract: Despite the need for preserving the carbon pools in fire-prone southern European landscapes, emission reductions from wildfire risk mitigation are still poorly understood. In this study, we estimated expected carbon emissions and carbon credits from fuel management projects ongoing in Catalonia (Spain). The planning areas encompass about 1000 km2 and represent diverse fire regimes and Mediterranean forest ecosystems. We first modeled the burn probability assuming extreme weather conditions and historical fire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Carbon Offset Revenue Alcasena et al, 2021 [12] x x Buckley et al, 2014 [34] x x Huang et al, 2013 [39] x x Pacheco & Claro 2021 [40] x x Penman et al, 2020 [41] x…”
Section: Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon Offset Revenue Alcasena et al, 2021 [12] x x Buckley et al, 2014 [34] x x Huang et al, 2013 [39] x x Pacheco & Claro 2021 [40] x x Penman et al, 2020 [41] x…”
Section: Studiesmentioning
confidence: 99%
“…Another potential stream of revenue from fuel treatments could come from the generation and marketing of carbon credits. Studies in Arizona [39], Australia [41], California [34], and Spain [12] found loss of carbon during wildfire could be averted due to fuel treatments, leading to justification of carbon credits. However, only one study in southern Europe [40] found that the potential revenue from carbon credits could be sufficient to fully offset the cost of fuel treatments.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation